Effect of an individualized bismuth quadruple regimen guided by 10-day or 14-day antibiotic susceptibility testing for first-line eradication treatment of Helicobacter pylori in Ningxia, China - Su, Xiaoming; Deng, Yanhong; Chen, Xianmei; Li, Yanling; Hao, Qian; Tang, Yuanyuan; Mu, Rui; Wu, Yuting; Zhou, Yan; Hu, Shengjuan (Frontiers in Medicine, 2025)
IntroductionHelicobacter pylori (H. pylori) is becoming more resistant to antibiotics, and the implementation of individualized therapy is highly valuable for its eradication. This study aimed to investigate the efficacy and safety of individualized treatment guided by antibiotic susceptibility testing (AST) with a 10-day or 14-day course for the eradication of H. pylori.MethodsThis was a prospective, open-label, single-center, quasi-randomized trial in which 220 participants were randomized into groups based on AST results as AST-10-day (n = 98) and AST-14-day (n = 112) treatment groups. All participants were retested for a 14-carbon urease breath test at weeks 4–8 after the end of the treatment.ResultsThe primary resistance rates of H. pylori to metronidazole, levofloxacin, clarithromycin, and amoxicillin were 94.1% (207/220), 42.7% (95/220), 41.4% (91/220), and 0.9% (2/220), respectively; however, no resistance to furazolidone and tetracycline was observed. In the AST-10-day and AST-14-day groups, the intention-to-treat (ITT) eradication rates were 89.8% (88/98) and 90.2% (110/122), respectively, with no statistically significant difference (p = 0.928). The per-protocol (PP) eradication rates were 92.6% (88/95) and 98.2% (110/112), respectively, with a statistically significant difference (p = 0.049). The incidence rates of adverse events (AEs) in the AST-10-day and AST-14-day groups were 6.3% (6/95) and 7.2% (8/112), respectively, with no statistically significant difference (p = 0.813). No statistically significant difference was observed in compliance between the two groups (p = 0.467).ConclusionBoth 10-day and 14-day AST guided individualized therapy can achieve satisfactory eradication effect. Compared with the 14-day regimen, the 10-day regimen has similar eradication rate and incidence of adverse events and compliance but shorter duration and lower cost.